Pembelajaran Kreatif Tari Jaipong Tingkat Anak Usia Dini: Tinjauan pada Sanggar Kartika Chandra Kirana Bekasi - Nikita, Listy Pregita Aidani; Sari, Anggy Murtrias (Universitas Hamzanwadi, 2024)
The education system in Indonesia consists of three important sub-systems: formal, informal and non-formal education. The main focus in this research is non-formal education, which has become an alternative for those who wish to explore their talents and interests outside the scope of formal education. This research highlights the significant role of dance studios as a form of non-formal education that has experienced rapid development in Indonesia, especially in big cities such as Bekasi. The Kartika Chandra Kirana dance studio is a type of non-formal education that has an important role in preserving Indonesian arts and culture, especially in the context of dance. The aim of learning dance at this studio is not only focused on developing technical skills, but also on understanding and appreciating cultural values ​​and can increase the creativity of young children. In the learning process, this studio applies various learning methods, including cooperative methods, peer tutoring, demonstrations, discussions and lectures. Students are also evaluated regularly, including through participation in the Jaipong Dance competition at Taman Mini Indonesia Indah every six months. Through these various learning and evaluation methods, students can develop their dance skills, increase self-confidence, and gain a deeper understanding of Indonesian culture. In this way, Sanggar Kartika Chandra Kirana plays a role not only as a place for dance learning, but also as a forum for preserving and developing Indonesia's cultural heritage and forming students' character holistically.